(untitled) (Medical Forum Monthly, 2024)
Objective: The present study was designed with an objective to assess the outcomes of antibiotics as primary treatment versus appendectomy in uncomplicated acute appendicitis (UAA). Study Design: Observational study Place and Duration of Study: This study was conducted at the Department of Surgery, PUMHSW Nawabshah from 2014 to April 2016. Materials and Methods: A sample of 227 diagnosed cases of acute appendicitis of both genders, age 16 - 60 years, clinical history and clinical signs of appendicitis with positive findings on Ultrasonography and increased leukocyte counts were the inclusion criteria. Study subjects were divided into group A and B on the basis of modified Alvarado score. Patients <4 score Alvarado score was exclusion criterion. Data was analyzed on SPSS 22.0 (P≤0.05). Results: During of pain and analgesic consumption was significantly higher in the group B as compared to group A in initial 2 days after surgery (p=0.001). However, the intensity of pain started decreasing after 2 days in group A and 4 days in group B, and this difference disappeared at one-month follow up. Hospital stay was lengthy in group B and surgical site infections were comparatively higher in group A patients. Mean cost therapy was expensive in group B compared to group A. Conclusion: The present study concludes the antibiotic therapy as safe and effective alternate to appendectomy in uncomplicated acute appendicitis with low recurrence rate and cost.